Prevalence and associated factors of depression, anxiety and stress among clinical therapists in China in the context of early COVID-19 pandemic - Tao, Rui; Li, Wenzheng; Min, Kaiyuan; Mo, Daming; Geng, Feng; Xia, Lei; Liu, Tingfang; Liu, Yuanli; Jiang, Feng; Liu, Huanzhong; Tang, Yi-lang (Frontiers in Psychiatry, 2024)
Objectives: To study the socio-demographic characteristics and the prevalence of depression, anxiety, and stress among clinical therapists in China during the early Coronavirus disease 2019 (COVID-19) pandemic and to identify associated factors.This cross-sectional study was part of a multicenter, nationally representative survey conducted through WeChat from January 2021 to March 2021. Data, including socio-demographics, health-related behaviors, and information on whether they participated in the frontline work of treating COVID-19, were collected anonymously.Respondents also completed the Depression Anxiety Stress Scales-21 (DASS-21).Results: In total, 396 clinical therapists in the selected hospitals completed the questionnaires, with a response rate of 89.0%. Respondents were predominantly female (77.3%). About 6.6% of the participants were current tobacco users, and 20.7% had participated in the frontline work of treating COVID-19. Overall, 22.0%, 17.9%, and 8.8% of participants were classified as having clinically meaningful depression, anxiety, and stress, respectively, based on DASS-21 scores. Multiple logistic regression in Model 1 and Model 2 showed that depression, anxiety, and stress were associated with regular physical activity and frequent insomnia (all, p < 0.05). In anxiety model 2, the associated factors for anxiety during the pandemic were identified as education (master's degree or more, OR=0.520; 95% CI=0.283-0.955), marital status (single, OR=2.064; 95% CI=1.022-4.168), tobacco use (OR=4.265; 95% CI=1.352-13.454), regular physical activity (OR=0.357; 95% CI=0.192-0.663), frequent insomnia (OR=6.298; 95% CI =2.522-15.729), and participation in the frontline work of treating COVID-19 (OR=3.179; 95% CI=1.697-5.954). The COVID-19 epidemic did not significantly increase the depression and stress levels among clinical therapists, but it did significantly increase anxiety levels.: During the COVID-19 pandemic, depression, anxiety and stress were relatively common among clinical therapists in China. Regular physical activity and good sleep were important protective factors against emotional problems. Therefore, encouraging regular physical activity and actively addressing clinical therapists' sleep problems is beneficial to improving the ability to cope with negative emotions. The COVID-19 epidemic significantly increased anxiety, and awareness and interventions should be recommended to reduce anxiety among clinical therapists during the COVID-19 pandemic.